2013
DOI: 10.4103/0972-0707.120952
|View full text |Cite
|
Sign up to set email alerts
|

Marginal sealing ability of silorane and methacrylate resin composites in class II cavities: A scanning electron microscopic study

Abstract: Aim and Objectives:To comparatively evaluate the microleakage and microgap formation along the gingival margin in class II cavities restored with silorane resin composite and methacrylate resin composite with and without flowable resin liner.Materials and Methods:Sixty human mandibular premolars were distributed into three groups, each group containing 20 teeth (n = 20). Mesial (subgroup A) and distal (subgroup B) box cavities were prepared with gingival margin above and below cemento enamel junction (CEJ), re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
1
8
0
1
Order By: Relevance
“…Another important consideration in the results of this study is a better marginal seal of cavities restored with silorane-based composite resin compared to dimethacrylate-based composite resin, consistent with the results of studies by Bechtold et al, 36 Nanjundasetty et al, 37 Krifka et al 38 and Bin Hasan and AL Saif, 39 who reported a better performance of silorane-based composite resins in terms of marginal adaptation. However, Arslan et al 12 did not report any differences between these two composite resin types, which was attributed to the nano-filled nature of the used dimethacrylate-based composite resin.…”
Section: Discussionsupporting
confidence: 89%
“…Another important consideration in the results of this study is a better marginal seal of cavities restored with silorane-based composite resin compared to dimethacrylate-based composite resin, consistent with the results of studies by Bechtold et al, 36 Nanjundasetty et al, 37 Krifka et al 38 and Bin Hasan and AL Saif, 39 who reported a better performance of silorane-based composite resins in terms of marginal adaptation. However, Arslan et al 12 did not report any differences between these two composite resin types, which was attributed to the nano-filled nature of the used dimethacrylate-based composite resin.…”
Section: Discussionsupporting
confidence: 89%
“…Various techniques and materials have been advocated for prevention of marginal gaps in this critical portion such as the use of centripetal build-up technique for incremental additions, compomers, low shrinkage composite[ 4 ] or use of stress breaking liners referred to as sandwich technique. The sandwich technique is a layering of materials to create the optimal combination of desirable properties in a restoration.…”
Section: Introductionmentioning
confidence: 99%
“…The silorane-based composite revealed decreased water sorption, solubility and associated diffusion coefficient compared with conventional methacrylate RBCs. [ 3 ] Nanjundasetty et al .,[ 4 ] have shown superior marginal integrity both below and above the CEJ with siloranes compared to methacrylate-based composites.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] Dye penetration tests have proved silorane-based composites to show significantly less microleakage at both the resin-enamel and resin-cementum interface. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%